The role of NLRP3 inflammasome in infection-related, immune-mediated and autoimmune skin diseases. Issue 3 (June 2020) - Wang, Dan; Duncan, Brittany; Li, Xizhe; Shi, Jian
Highlights: Abnormal expression of NLRP3 play an important role in infection-related, immune-mediated and autoimmune skin diseases. Abnormal activation of NLRP3 inflammasome is related to a variety of common skin diseases. NLRP3 gene mutations and polymorphisms linked to multiple skin diseases. NLRP3 inflammasome targeting regulatory drugs can significantly improve the condition of skin diseases. Abstract: Inflammasomes are large intracellular multi-protein signaling complexes which are responsible for the activation of inflammatory responses. Among multifarious subtypes of inflammasomes, NLRP3 has been associated with a variety of inflammatory and autoimmune skin conditions, including dermatophytosis, psoriasis, acne, urticaria and bullous pemphigoid and other different skin diseases which have been a subject of intensive investigation. NLRP3 is considered to be a sensor of microbial and other danger signals and plays a crucial role in immune responses, dysregulation of NLRP3 inflammasome activation is involved in skin diseases. With the in-depth research, targeting NLRP3 inflammasome and its downstream signaling will provide new insights into the development of future therapeutic strategies. In this review, we summarize the molecular mechanism of NLRP3 inflammasome activation as well as the current knowledge on the contribution of the NLRP3 inflammasome in infection-related, immune-mediated and autoimmune skin diseases.